2022
DOI: 10.3748/wjg.v28.i47.6769
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-related protein 1/cytoskeleton-associated protein 4 signaling activation by Helicobacter pylori-induced activator protein-1 promotes gastric tumorigenesis via the PI3K/AKT/mTOR pathway

Abstract: BACKGROUND Gastric cancer (GC) is a common malignant tumor with high incidence and mortality rates globally, especially in East Asian countries. Helicobacter pylori ( H. pylori ) infection is a significant and independent risk factor for GC. However, its underlying mechanism of action is not fully understood. Dickkopf-related protein (DKK) 1 is a Wnt signaling antagonist, and cytoskeleton-associated protein (CKAP) 4 is a newly identified DKK1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Our transcriptomic analysis revealed that in H. pylori-infected GES-1 cells, the expression of AP-1 related genes such as FOS, FOSB, FOSL1, FOSL2, and JUN, was statistically increased with respect to both non-infected and TNF-treated cells. Of note, DKK1, the gene encoding the Dickkopf-related protein, which was recently identified as a target of H. pylori activated AP-1 signaling [38], was upregulated as well in infected GES-1 cells in comparison to either non-infected or TNF-treated cells. Thus, it may be concluded that AP-1 signaling is operating in H. pylori infected GES-1 cells also due to direct increased expression of this set of transcription factors.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our transcriptomic analysis revealed that in H. pylori-infected GES-1 cells, the expression of AP-1 related genes such as FOS, FOSB, FOSL1, FOSL2, and JUN, was statistically increased with respect to both non-infected and TNF-treated cells. Of note, DKK1, the gene encoding the Dickkopf-related protein, which was recently identified as a target of H. pylori activated AP-1 signaling [38], was upregulated as well in infected GES-1 cells in comparison to either non-infected or TNF-treated cells. Thus, it may be concluded that AP-1 signaling is operating in H. pylori infected GES-1 cells also due to direct increased expression of this set of transcription factors.…”
Section: Discussionmentioning
confidence: 96%
“…It is known that H. pylori infection leads to activation of the activator protein 1 (AP-1) cascade [37] and to increased expression of members of this family of transcription factors [38]. Our transcriptomic analysis revealed that in H. pylori-infected GES-1 cells, the expression of AP-1 related genes such as FOS, FOSB, FOSL1, FOSL2, and JUN, was statistically increased with respect to both non-infected and TNF-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection is a well-known factor that contributes to the genesis and development of GC. Recent evidence has shown that DKK1 transcription could be induced by H. pylori infection and further lead to gastric tumorigenesis via activation of the CKAP4/PI3K/AKT/mTOR pathway [49]. Herein, identifying small molecule drugs or antibodies blocking the DKK1/CKAP4 axis could be an important aspect of GC treatment.…”
Section: Discussionmentioning
confidence: 99%